Brutalization Revisited: The Case of Russia. (January 2015) - Beyrau, Dietrich
In the case of Russia, the existence of a relationship between lost war, revolution, and Civil War is obvious. Unlike the German case, however, it has not been investigated in any detail. The Great War is often seen as the 'forgotten war' in the shadow of the Revolution of 1917 and the Civil War of 1918–21. Inspired by George Mosse's work on Germany, this article investigates the connections between these conflicts. It argues that it is not easy to reconstruct the direct linkages between the fronts of an industrialized war to the violence of revolution and civil war. Rather, enduring traditions were transferred, transformed, and radicalized: the style of rule, the result of an absent political and patriotic consensus between the heterogeneous communities of communication, and dispositions to violence among the decisive sectors of the population, not only the soldiers and the revolutionaries, but also the peasants and workers longing for an egalitarian and just economy. The main role of the war was that it destroyed the old state and set these pre-existing violent tendencies free, which began to feed on themselves.